The Relationship Between Gender-Responsive and Culture-Based Learning on the Education Quality of Higher Education - Masnun, Masnun; Fadli, Adi (FKIP Universitas Lampung, 2024)
Abstract: The Relationship Between Gender-Responsive and Culture-Based Learning on the Education Quality of Higher Education. Objectives: This study aims to determine the relationship between gender-responsive and culture-based learning on the quality of education in tertiary institutions. Methods: This study involved 400 students and educators from 10 tertiary institutions. This survey study adopted a cross-sectional survey design. The data were collected using non-test methods and the data were analyzed using multiple linear regression tests. Findings: The results showed that (1) there is a significant relationship between gender-responsive learning and the quality of tertiary education with a percentage of 35.4%; and (2) there is a significant relationship between cultural-responsive learning and the quality of higher education with a percentage of 38.4%. Conclusion: There is a significant relationship between gender and cultural-responsive learning simultaneously with the quality of tertiary education with a percentage of 61.4%. Keywords: gender-responsive learning, cultural-responsive learning, quality of education, higher education.DOI: http://dx.doi.org/10.23960/jpp.v14.i1.202402